Proposed business strategy of pt. Pancar garis cahaya in housing market for urban middle-class millennials - Bintang Arigia, Muhammad; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2018)
Abstract. Residential property in Indonesia is set to be overwhelmed with demands as urban middle-class millennials has been just entering the productive age and become a strong prospective market with its massive number and delightful characteristics for the industry. The opportunity becomes even better as currently, Indonesia has 11.4 million house shortage and is increasing for about 800.000 units every year. The biggest ratio of Indonesian backlog in 2016 happen in Jakarta, the number is almost half of the total Indonesian backlog, which is 49.84%. However, latest trends show that the urban middle-class millennials are facing difficulty regarding their buying power to buy their own house. The problem caused by the average increase of people’s earnings is far below the rise of property price. PT. Pancar Garis Cahaya, a general contractor that specializes in civil engineering related products/services tries to aim and capture the prospective market as the company plans to offer a house that will fit with urban middle-class millennials style, preferences, and budget. The research discusses the business strategy of PT. Pancar Garis Cahaya in its plan to capture the market. External and internal analysis is done to discover the whole situation regarding the business issue and formulate the business strategy by using Porter’s generic business strategy, tows matrix, diamond strategy, and business model canvas. The results of this research are that the opportunity is real, there are a big undeserve market. The company also has the significant power to help them produce decent house for the urban middle-class millennials housing market, which are deep knowledges in house making, experienced workers, good partnership with suppliers and banks, effective work ethics, etc. However, the company need a big improvement on marketing efforts to increase its brand awareness and sales through marketing public relations. Furthermore, cost leadership strategy is the most suitable strategy to this price sensitive industry.Keywords:  housing, Indonesia, millennials, property, residential.